A micro-grid operation analysis for cost-effective battery energy storage and RES plants integration. (15th October 2016) - Barelli, L.; Bidini, G.; Bonucci, F.
Abstract: Penetration of renewable energy is strongly slowed by its characteristic intermittency and fluctuating trend and by the inadequacy of electricity networks. These issues can be addressed through the development of new or improved storage technologies with higher performance, availability, durability, safety and lower costs. In the present work, micro-grids characterized by the presence of different subsections including renewable plants coupled with batteries storage solution are investigated through the development of a suitable code. Several design conditions and features, related to RES plant, storage system and users, were considered in order to realize a sensitivity analysis aimed to examine, on a yearly base and with one minute time step, interactions among the different micro-grid subsections and to identify the best solutions from both economic and energy point of views. Highlights: Storage systems coupling to RES plants is investigated for micro-grids. Interactions between RES plants, storage batteries and users are analyzed. Self-consumption increases with storage installation. Investment pay-back analysis is performed varying plant configurations. Pay-back reduction up to 30–40% for new RES/Storage integrated installations.